2020
DOI: 10.1073/pnas.1920546117
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan PHD2 , an allele with loss-of-function properties

Abstract: Tibetans have adapted to the chronic hypoxia of high altitude and display a distinctive suite of physiologic adaptations, including augmented hypoxic ventilatory response and resistance to pulmonary hypertension. Genome-wide studies have consistently identified compelling genetic signatures of natural selection in two genes of the Hypoxia Inducible Factor pathway,PHD2andHIF2A. The product of the former induces the degradation of the product of the latter. Key issues regarding TibetanPHD2are whether it is a gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…2014 ; Song et al. 2014 , 2020 ). In vitro experiments revealed that the two mutations impair PHD2: p23 binding ( Song et al.…”
Section: Genetic Experiments Provide Insights Into Mechanism and Procmentioning
confidence: 99%
“…2014 ; Song et al. 2014 , 2020 ). In vitro experiments revealed that the two mutations impair PHD2: p23 binding ( Song et al.…”
Section: Genetic Experiments Provide Insights Into Mechanism and Procmentioning
confidence: 99%
“…One exception is at the EGLN1 gene, whereby variants in the first exon found at high frequency in Tibetans (Asp4Glu; Cys127Ser) are reported to result in a gain of PHD2 function, which leads to increased HIF degradation under hypoxic conditions and erythroid progenitor disruption (Lorenzo et al, 2014). Other reports suggest these variants underlie a loss of PHD2 function via defective binding of co-chaperone p23 that would lead to increased HIF activity (Aggarwal et al, 2010;Song et al, 2014) and possibly ventilatory responses (Song et al, 2020).…”
Section: Shared Signatures Of Adaptation Within and Across Himalayanmentioning
confidence: 99%
“…Tibetans harbor a C127S substitution in PHD2 that, in the context of the WT protein, is without an appreciable effect in vitro . However, in the context of a D4E mutation that is adjacent to the PHD2 zinc finger, the C127S substitution results in markedly impaired interaction of PHD2 with the HSP90 cochaperone p23, leading to loss of function ( 29 , 30 ). We propose that the high-altitude deer mouse T755M Hif-2α mutation and the human Tibetan C127S PHD2 substitution represent two independent adaptive amino acid changes in the HIF pathway that occur in potentially disordered regions of the respective proteins, produce loss of function in the context of other selective amino acid changes, and promote adaptation to the chronic hypoxia of high altitude.…”
Section: Resultsmentioning
confidence: 99%